On the Empresses of the Latin Empire (1204–1261) (1). Maria the countess of Champagne - Pentek, Zdzisław (Balcanica Posnaniensia. Acta et studia, 2020)
This article is the first one in the planned series “On the Empresses of the Latin Empire (1204-1261)”. This one is dedicated to Maria, the countess of Champagne, who, having set off on a crusade, reached Akka, and there she learned about the election of her husband, Count Baldwin Flanders to be the first Latin emperor. The text presents her biography and highlights her participation in the crusades of her relatives.